PERTUMBUHAN BIBIT KAKAO (THEOBROMA CACAO.L) DENGAN PEMBERIAN BEBERAPA DOSIS PUPUK NPK (16:16:16) PADA TANAH ULTISOL DI POLYBAG - Ridawati Marpaung (Jurnal Ilmiah Universitas Batanghari Jambi, 2013)
This study aims to determine the growth response to soil ultisol cocoa seedlings in polybags with fertilizer NPK (16:16:16) and to determine the dose of fertilizer NPK (16:16:16) which can give a better effect on the growth of cocoa seedlingsThe research was carried out at RT: 01 Pakuan New South Jambi District. For 6 months. This research used Completely Randomized Design (CRD) with 5 standard treatment, consisting of: T0 = Without Giving NPK (16:16:16), T1 = NPK fertilizer (16:16:16) at a dose of 2.5 g, T2 = fertilizer NPK (16:16:16) at a dose of 5 g, T3 = fertilizer NPK (16:16:16) at a dose of 7.5 g, T4 = fertilizer NPK (16:16:16) at a dose 10 g. Treatment was repeated four times so that there are 20 plots of each treatment plot consisted of 3 plants, so there are 60 plants, 2 plants per plot were taken as samples. The parameters measured were plant height stem diameter, total leaf area, canopy dry weight, root dry weight, root crown ratio.The results showed that fertilizer NPK (16:16:16) at a dose of 10 g (T4) provides the best results for plant height, stem diameter 26.27% 16.98%, 68.34% total leaf area, canopy dry bert 195 , 09%, 76.31% dry weight of roots and root crown ratio is 66.67% when compared with no treatment (T0 / Control)Keywords: Growth, NPK fertilizer, cocoa seeds.